HUBUNGAN ANTARA KONFORMITAS DENGAN KECENDERUNGAN PERILAKU CYBERBULLYING PADA COSPLAYER DI KOMUNITAS COSPLAY SEMARANG (COSMA) - Kinari Arya Apsari; Siswati Siswati (Faculty of Psychology, Diponegoro University, 2020)
The purpose of this research is to determine the relationship between conformity and cyberbullying tendency on cosplayersat Cosplay Semarang (COSMA) community. The population in this researchwere 191cosplayers with123research samples was chosen using convinience sampling technique. The method used to collect data is consisted of two psychological scales, that are Cyberbullying Tendency Scale (34 items, α= 0,909) and Conformity Scale (33 items, α= o,882). Pearson’s Product Moment Analyze is used to analize the collected data. The analyzed data show that correlation coefficient (rxy) is 0,584 (p<0,001), it shows that there is a significant positive relationship between conformity with cyberbullying tendency among cosplayers. The increasing level of effective conformity, means increasing level of cybebrullying tendency and vice versa. Conformity contribute 34,1% to cyberbullying tendency, with 65,9% from another factor that is not measured in this research.